Worker well-being - Polachek, S. W. (Emerald, 2000)
How do technology, public works projects, mental health, race, gender, mobility, retirement benefits, and macroeconomic policies affect worker well-being? This volume contains fourteen original chapters utilizing the latest econometric techniques to answer this question. The findings include the following: technology gains explain over half the decline in U.S. unemployment and over two-thirds the reduction in U.S. inflation; universal health coverage would reduce U.S. labor force participation by 3.3 per cent; blacks respond to regional rather than national changes in schooling rates of return, perhaps implying a more local labor market for blacks than whites; employee motivation enhances labor force participation, on-the-job training, job satisfaction and earnings; male and female promotion and quit rates are comparable once one controls for individual and job characteristics; public works programs designed to increase a worker's skills do not always increase reemployment; and, U.S. pension wealth increased about 20 per cent - 25 per cent over the last two decades.
Keywords: Labor economics.; Labor supply -- United States.; elektronické knihy; electronic books